Current Technology in Hip Replacement - Phatama, Krisna Yuarno (Indonesian Hip and Knee Society (IHKS), 2024)
Hip replacement, also known as total hip arthroplasty (THA), is widely regarded as an incredibly effective surgical procedure, often hailed as a ground-breaking achievement in medicine.1 The initial development of total hip replacement dates back to 1938 when Wiles made significant progress.2 However, it wasn't until the 1960s that this procedure gained widespread recognition and popularity. Sir John Charnley's introduction of